Strategic Management in Quality Improvement at State Madrasah - Mustapid Mustapid; Syafaruddin Syafaruddin; Candra Wijaya (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to analyze strategic planning, policy implementation and evaluation of quality improvement programs at a State Madrasah Aliyah Medan. This study uses a qualitative approach with data collection techniques through interviews, observation and documentation. While strengthening the validity of the data from research findings, the use of data validity standards based on Lincoln Guba consists of credibility, transferability, dependability, and confirmability. The results of this study indicate that; 1) strategic planning in quality improvement is carried out by deliberation and teamwork to formulate the madrasa's vision and mission, analysis of the internal environment of the resources owned by the madrasa and the external environment of the madrasa environment both geographically, socio-culturally and economically, analysis of strategy selection and the key to success appropriate, and strategy selection; 2) Implementation of madrasa policies in quality improvement is carried out by implementing education quality improvement programs and adopting policies to carry out continuous process improvements, establishing quality assurance and quality standards for quality improvement, creating a madrasa culture or culture, making organizational changes and maintaining good relations with stakeholders both central government, regional and community; and 3) Evaluation of the quality improvement program is carried out through monitoring all the results of planning and implementation, measuring the performance of individuals and madrasah institutions, compiling reports on the implementation of activities and taking corrective steps.